The acts of the EU tax law and double tax treaties: the problems of correlation in establishing anti-tax avoidance rules - E. A. Ponomareva (Правоприменение, 2022)
The subject. The specifics of the functioning of tax systems and the risk of double taxation require a solution to the issue of whether tax competence can remain only at the national level. Modern cross-border tax relations operate within a multi-level system of legal regulation based on the norms of international, supranational and national lawThe difficulties of correlating these levels are rooted in the fact that, in accordance with international law, each State has the right to tax persons or transactions with which it has a sufficient connection. Different situations may occur when both countries believe that the taxpayer is their resident, or when each of them claims that the income was received in this state. States solve this problem both unilaterally with the help of national legislation, and on a bilateral basis with the help of a double tax treaty.With the adoption of the Action Plan aimed at combating the erosion of the tax base and the withdrawal of profits (hereinafter referred to as the BEPS plan) and the EU Council Directive 2016/1164 (ATAD), tax strategies for using gaps and inconsistencies in tax rules to artificially transfer profits to low-tax jurisdictions were limited.Purpose of the study. The article discusses possible scenarios arising from the interaction of tax agreements and acts of EU tax law. It is necessary to take into account the obligation of the Member States to eliminate inconsistencies between acts of national legislation and acts of EU law. Member States have committed to achieve this goal at the time of EU accession and, therefore, before the adoption of any secondary EU law.Methodology. The research was carried out with the application of the formally legal interpretation of legal acts as well as the comparative analysis of international and European legal literature. Structural and systemic methods are also the basis of the research.The main results. Due to the clear coordination between the European Union and the OECD of actions in terms of establishing common measures to combat tax evasion and focusing on the subjective element of assessing potential abuse situations, a new standard for combating tax evasion has been established.Сonclusions. The author comes to the conclusion that the priority of the EU law over DTTs has been established. However, Member States retain the right to establish their own tax regimes and enter into tax treaties, thereby creating conflicts in legal regulation. In order to be directly applicable, the norm of the treaty must be clearly and definitely formulated, as well as be unconditional and independent of any national implementation measures.National legislation provides measures to eliminate the legal multiple taxation only for its residents. On the other hand, with respect to tax agreements concluded with third countries, the predominance of one system over another depends on the specific scenario, and in some cases the result achieved is the result of interpretation of existing provisions. In particular, tax treaties should prevail only when concluded before a state joins the EU.